STRATEGI DALAM INTEGRASI PENDIDIKAN KARAKTER BERLANDASKAN NILAI-NILAI ISLAM DALAM PEMBELAJARAN IPS DI ERA 5.0 - Ita Maulana Zakiyah (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
The digital era has a major impact on students' behavior and character, including at the elementary school level. Easily accessible information and the instant culture of social media have shifted students' ethical and moral values, causing increasingly worrying moral degradation. This study aims to examine the importance of integrating character education in social studies learning in the 5.0 era. The method used is a literature study with a qualitative approach. The results of the study show that the integration of character values ​​in social studies, such as responsibility, honesty, mutual cooperation, and empathy, can be a strategic solution to build students' character. These values ​​are inserted through materials, learning activities, and evaluations. Although there are various challenges, such as lack of teacher understanding and environmental influences, strengthening character in social studies learning has proven to be relevant in preventing moral degradation and forming an ethical and responsible generation.